A case study from a nursing and occupational therapy perspective – Providing care for a patient with a traumatic brachial plexus injury. Issue 1 (February 2015) - Wellington, Beverley; McGeehan, Claire
Abstract This paper presents a case study that demonstrates how collaborative working between professionals enhanced the holistic care for a patient following a traumatic brachial plexus injury. The paper will describe the patient's journey of care from initial presentation, diagnosis and assessment, acute care provision, discharge & rehabilitation to ongoing supportive counselling. The care encompasses input from both a nursing and occupational therapy perspective.